"I Am Queer Because I Am Armenian": On the Queerness of Racially Ambiguous Diasporic Belonging. Issue 1 (29th April 2021) - Sargsyan, Nelli
Abstract: What does it mean to be of a diaspora, when you are displaced from the Black/Person of Color/white racial paradigm due to its inadequacy, at the same time as you are displaced from your diasporic ethnolocality due to your queer desire? Drawing on the discourses of queer Armenian American diasporic women, I argue that in order to understand queer ethno‐diasporic belonging we need to think of queer desire and racially ambiguous ethnolocality in tandem. Diasporic ethnolocality and queer desire simultaneously mark each other as (in)commensurable and animate each other, because for queer Armenian women the desire for ethno‐diasporic belonging emerges at the site of displacement from diasporic ethnolocality due to queer desire. Queer Armenian women's diasporic belonging illuminates the fact that queer desire and diasporic ethnolocality are in an indeterminate relationship that is always dependent on the kinds of "open‐ended entanglements" (Tsing 2015, 83) that gather in place at a given moment and points to the unfinished and situational project of diasporic belonging in general. By engaging the discourses of queer women of different migratory generations I refuse multiple queer erasures—of lived experiences of racially ambiguous ethnolocality and of the livable lives disrupting diasporic normativities.